(untitled) (Ustozlar uchun, 2025)
This article explores the theoretical and practical aspects of translating newspaper texts, emphasizing the linguistic, cultural, and ideological challenges involved in the process. Newspaper translation plays a vital role in global communication, as it helps transmit news, ideas, and viewpoints across linguistic and cultural boundaries. The study discusses the stylistic and structural features of newspaper language, the influence of ideology, and the translator’s role as a mediator between cultures.